Long-term monitoring of deoxynivalenol in Serbian maize: A 2010-2023 study - Polovinski-Horvatović, Miroslava; Krstović, Saša; Jajić, Igor; Guljaš, Darko; Damjanović, Marko; Cokoski, Kristijan (Centre for Evaluation in Education and Science (CEON/CEES), 2025)
The trichothecenes are a diverse group of mycotoxins primarily produced by molds from the Fusarium genus, and can occur both in the field and in storage units. In this study, a total of 576 samples were processed over a 14-year period, from 2010 to 2023. The number of samples in which some concentration of deoxynivalenol (DON) was detected was 288. The average value during the observed period (2010-2023) ranged from 0.176 in 2020 to 2.420 mg/kg in 2014. The highest concentration was recorded in 2014 at 9.498 mg/kg, while other maximum values in different years reached up to 3.822 mg/kg. The occurrence of DON varies from year to year, primarily depending on climatic conditions. The number of positive samples ranged from 5% in 2018 to 100% in 2014. However, contamination of maize with Fusarium can happen not only in the field but also during storage. Therefore, continuous monitoring is necessary. Our findings suggest that the presence of DON may affect animal production; this impact may have been overlooked due to other pressing issues.